(untitled) (Studia Prawnicze / The Legal Studies, 2019)
The article’s objective is to present the essence of the system of extraordinary remedies in the Polish civil procedure, as well as a characterization of the particular remedies comprising that system. Application of the dogmatic method has also verified the hypothesis according to which the Polish legislator, in giving those remedies (including extraordinary ones) a normative structure, has in view that their objective is to seek a change in or to set aside the contested ruling. The article accents particularly regulation of the extraordinary grievance, considering its status as novel legislation giving rise to numerous doubts and reservation, as the normative shape of that remedy constitutes a source of collision between two values – the stability if a judicial ruling, and its lawfulness. The emergence of this remedy has led to the conclusion that there is a need to review the existing position of the civil procedure doctrine concerning respect for the principle of exclusivity adopted in our system of remedies. Celem artykułu było przedstawienie istoty systemu nadzwyczajnych środków zaskarżenia w polskim postępowaniu cywilnym, a także scharakteryzowanie poszczególnych środków składających się na ten system. W wyniku zastosowania metody dogmatycznej zweryfikowano też tezę, według której, ustawodawca polski nadając normatywny kształt środkom zaskarżenia, w tym także nadzwyczajnych, ma na względzie, że mają one zmierzać do uzyskania zmiany lub uchylenia zaskarżonego orzeczenia. W rozważaniach zaakcentowano zwłaszcza regulację skargi nadzwyczajnej ze względu na to, że mamy tu do czynienia z nowością legislacyjną, która wzbudza wiele wątpliwości i zastrzeżeń, gdyż kształt normatywny tej skargi jest źródłem kolizji dwóch wartości – stabilności orzeczenia sądowego i jego praworządności. W związku z tą skargą nasunął się wniosek, że istnieje potrzeba zrewidowania dotychczas prezentowanego w doktrynie procesu cywilnego stanowiska co do respektowania przyjętej w naszym systemie środków zaskarżenia zasady wyłączności.